Trayectorias laborales de migrantes calificadas por razones de estudio - Bermúdez Rico, Rosa Emilia (El Colegio de México A.C., 2014)
This article analyzes the career paths of a number of Columbian university women who have pursued graduate studies in Mexico and explores the main patterns of their insertion in the professional labor market in both Colombia and Mexico. The focus is to examine the way these career paths have been shaped by the experience of mobility for the purpose of study during both the stage prior to international migration and the subsequent period, whether they remained in the country of destination or returned totheir country of origin. Within this context, the author analyzes the place occupied andthe meaning acquired by international mobility for the purpose of study in the careerpaths of university women. The analysis constitutes an exploratory case study basedon a qualitative research design, using the theoretical and methodological perspectiveof the life course. Longitudinal and retrospective information was compiled on thebasis of in-depth interviews with migrant women, making it possible to reconstructtheir biographies. The analysis shows that this group of women has used variousstrategies, including resistance and adaptation as alternative means of coping withthe professional labor market in Colombia and Mexico. This analysis was used toidentify four types of career paths involving a combination of decisions as to whetherremain in the host society or return to the country of origin, on the basis of two areasof knowledge.